Involvement of autophagy in the outcome of mitotic catastrophe - Sorokina, Irina V. (Sci Rep, 2017)
Evading cell death is a major driving force for tumor progression that is one of the main problems in current cancer research. Mitotic catastrophe (MC) represents attractive platform compromising tumor resistance to current therapeutic modalities. MC appeared as onco-suppressive mechanism and is defined as a stage driving the cell to an irreversible destiny, i.e. cell death via apoptosis or necrosis. Our study highlights that MC induction in colorectal carcinoma cell lines ultimately leads to the autophagy followed by apoptosis. We show that autophagy suppression in Atg 13 knockout non-small cell lung carcinoma cells lead to the dramatic decrease of MC rate. Furthermore, mitochondria-linked anti-apoptotic proteins Mcl-1 and Bcl-xL play a crucial role in the duration of MC and a cross-talk between autophagy and apoptosis. Thus, the suppression of apoptosis by overexpression of Mcl-1 or Bcl-xL affected MC and lead to a significant induction of autophagy in HCT116 wt and HCT116 14-3-3σ(−/−) cells. Our data demonstrate that MC induction is a critical stage, in which a cell decides how to die, while mitochondria are responsible for the maintaining the balance between MC – autophagy – apoptosis.